Horizontal Hostility among Non-Meat Eaters - Rothgerber, Hank (PLOS ONE, 2014)
The present study examined intergroup judgments made between four groups of non-meat eaters: health vegetarians; ethical vegetarians; health vegans, and ethical vegans. Consistent with hypotheses based on horizontal hostility and the need to maintain ingroup distinctiveness, ethical vegetarians gave unfavorable evaluations to health vegetarians relative to vegans, especially when the mainstream omnivore group was made salient. Contrary to expectations, vegans gave relatively more favorable evaluations to ethical vegetarians than health vegetarians when mainstream salience was low. This was especially true for vegans who were motivated primarily by ethical concerns. When mainstream salience was high, vegans did not distinguish between the vegetarian subgroups. Results suggest that one’s motives for abstaining from meat often play a larger role in this type of intergroup perceptions than one’s dietary practices.